Epidemiology of substance abuse in war survivors and their relatives - F. Dortaj (Afarand Scholarly Publishing Institute, 2009)
Introduction: war wounded (Janbazan) are people who need a new adaptation with their physical and social situations, because of their physical damages. Since, any terrible change in human life may result in psychological pressure Janbazan may be more willing to use drugs and substance abuse to cope with their physical and psychological damages. Aim: the main aim of this research was to find out the amount of drug addiction spreading among Janbazan in Kerman city in terms of the degree and the type of wounding, age and so on. Methodology: the type of this investigation is an applied and survey research. Statistical society comprised the entire Kerman city Janbazan who had war wounded file in Janbazan foundation. The sample included 400 who were randomly selected using classical sampling method. In order to assess the degree of addiction, addiction checklist and also population feature questionnaire were used. The data were statistically analyzed using Pearson correlation test and Spearman, Kendall, Mann-Whitney and Kruskal-Wallis respectively. Results: the results showed that 31% of the war wounded (Janbazan) had dependence to drug addiction. It was also found that thee is a meaning relationship between the degree of wounding, age, spouse and mother academic level, income, living costs, smoking and drug addiction